2022
DOI: 10.1080/15685551.2022.2054117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of chitosan based controlled release nanoparticles for the delivery of ticagrelor

Abstract: The aim of this contemporary work was to formulate a controlled release mucoadhesive nanoparticle formulation for enhancing the oral bioavailability of Ticagrelor (TG), a BCS class IV drug, having low oral bioavailability of about 36%. The nanoparticles can act as efficient carriers for hydrophobic drugs, due to having high surface area and hence can improve their aqueous solubility due to their hydrophilic nature. The nanoparticles (NPs) of TG were formulated using chitosan (CH) as polymer and sodium tripolyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…It can be used in pharmaceutical excipients or drug carriers [ 4 ], wound-healing materials [ 5 ], and as a scaffold for tissue engineering [ 6 ]. Chitosan is often used in pharmaceutical technology as an ingredient controlling and delaying the release of both synthetic [ 7 , 8 , 9 ] and natural ingredients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in pharmaceutical excipients or drug carriers [ 4 ], wound-healing materials [ 5 ], and as a scaffold for tissue engineering [ 6 ]. Chitosan is often used in pharmaceutical technology as an ingredient controlling and delaying the release of both synthetic [ 7 , 8 , 9 ] and natural ingredients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Shahid et al used XRD to predict the type of interaction within Ticagrelorloaded chitosan-based NPs [46]. Ahmad et al reported the use of XRD to study the crystallite structure within starch-based NPs prepared using mild alkali hydrolysis and an ultra-sonication process.…”
Section: Xrd Spectrum For Chitosan Polymer (Cs) Crosslinker (Stpp) Me...mentioning
confidence: 99%
“…The presence of specific chemical groups on the surface of the NBCs will also enable further functionalization by antibodies or by enzymes [41]. These properties greatly affect drug targeting resulting in site-specific drug delivery, for example, in tumor treatment [46].…”
Section: Nbc Surface Charge (Zeta Potential) Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a strong positive charge in solution, which can increase cancer cell uptake through interactions with the negatively charged cell membrane [ 15 ]. There are also several studies on chitosan nanoparticle systems that demonstrate its ability to release its payload more efficiently at an acidic pH [ 16 , 17 , 18 ], which is relevant for cancer treatment as the tumor microenvironment is reported to lie in the acidic pH range of 5.6–6.8 [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%